The effect of economic status on height, insulin-like growth factor (IGF)-I and IGF binding protein-3 concentrations in healthy Turkish children - BEREKET, ABDULLAH; ÖZEN, AHMET OĞUZHAN; HAKLAR, GONCAGÜL; DEMİRCİOĞLU, SERAP (NATURE PUBLISHING GROUP, 2007)
Objectives: The effect of economic status (ES) on growth, insulin-like growth factor (IGF)-I and IGF-binding protein (IGFBP)-3 in healthy children is not well characterized. We aimed to study the interrelationship between height, weight, IGF-I, IGFBP-3, mid-parental height (MPH) and ES. Design/ subjects: Eight hundred and fourteen healthy children (428 boys, 386 girls; age 3 -18 years) were classified according to income of the families as low, middle and high. Standard deviation scores (SDSs) of height, weight, MPH, IGF-I and IGFBP-3 were compared between the groups. The combined effect of these parameters and ES on height SDS was investigated with complex statistical models. Results: There was a significant trend for height and weight SDSs to increase with higher income levels in boys, but not in girls. Body mass index (BMI) SDSs were similar in three groups. There was a general trend for MPH SDS to increase with income levels in both sexes. In boys, IGF-I SDS was significantly higher in high ES group than low ES. In girls, IGFBP-3 SDSs were significantly higher in high ES group than in middle ES group. For both genders, height SDS was highly correlated with weight SDS and moderately correlated with BMI SDS, MPH SDS and IGF-1 SDS. All correlations were significant and positive. Complex models showed that MPH (19%), IGF-I (13%) and ES (3%) in boys, and MPH (16%) and IGF-I (7%) in girls have significant contribution to height SDSs. Conclusions: ES per se, independent of overt malnutrition, affects height, weight, IGF-I and IGFBP-3 with some gender differences in healthy children. Influence of income on height and weight show sexual dimorphism, a slight but significant effect is observed only in boys. MPH is the most prominent variable effecting height in healthy children. Higher height and MPH SDSs observed in higher income groups suggest that secular trend in growth still exists, at least in boys, in a country of favorable economic development.
Keywords: insulin like growth factor-I (IGF-I); insulin like growth factor binding protein-3 (IGFBP-3); economic status; growth; weight; height; BODY-MASS INDEX; FACTOR-I; SERUM-LEVELS; SOMATOMEDIN-C; NUTRITIONAL REGULATION; SANLIURFA PROVINCE; OBESE CHILDREN; HORMONE; ADULTS; SCHOOLCHILDREN